Analizar el comportamiento de las corrientes de falla por cortocircuito frente a diferentes conexiones de un transformador trifásico mediante la utilización d e un prototipo. - Quinatoa Yugcha, Nelson Ramiro (2019)
This project aimed to create a test module to make failures by short circuit, it has a bank of single-phase transformers and a bank of adjustable autotransformers. The bank of transformers allows making the different established connections with which to do a study about the behavior of single-phase, biphasic, biphasic faults to ground and three-phase. The module has a data acquisition system in which it can visualize the currents, voltages, phase shifts and phasor diagrams per connection group. For the different faults that can be made in the module, the input voltage must be regulated, to protect the bank of transformers that can withstand a maximum current of 6 A. The module also has the ability to make different connections allowing the analysis of the fault current in each scenario, the most relevant results obtained are the following: In a Dy5 connection, the current mismatch between the primary and secondary phase will be 150° under normal conditions, after a biphasic short circuit the current in phase C with 0.18A is disregarded, when compared with fault currents with 2.30 A, in terms of phase shifts the positive sequence current advances 90 ° to the fault current., while the current of negative sequence is delayed by 90 ° from the fault current.